2021
DOI: 10.31234/osf.io/rwcvq
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How Protective Buffering Harms Post-Divorce Adjustment in Parent-Adolescent Relationships

Abstract: After a divorce, parents and children try to minimize each other’s distress by hiding their feelings and pretending they are doing fine, a coping strategy called protective buffering (PB). Although there is substantial evidence that PB among romantic partners harms both partners’ well-being, the consequences of PB in parent-child relationships remain unclear. To examine PB among parents and children, we conducted a survey study among 100 dyads of Dutch divorced parents and their adolescent children. We examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
(85 reference statements)
0
1
0
Order By: Relevance
“…The dynamics of communicating stress and managing one's own stress are worth investigating. Also, as it was shown that protective buffering in parent-child dyads was associated with reduced authenticity, one possibility is that parents' and children's negative dyadic coping is associated with reduced feelings of authenticity, which in turn may hamper children's quality of life (van der Wal et al, 2021). Last, perceptions of the other person's dyadic coping may affect children's and parents' outcomes to a greater extent than one's own dyadic coping.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…The dynamics of communicating stress and managing one's own stress are worth investigating. Also, as it was shown that protective buffering in parent-child dyads was associated with reduced authenticity, one possibility is that parents' and children's negative dyadic coping is associated with reduced feelings of authenticity, which in turn may hamper children's quality of life (van der Wal et al, 2021). Last, perceptions of the other person's dyadic coping may affect children's and parents' outcomes to a greater extent than one's own dyadic coping.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%